„Nemůžeš být malířka, z tebe bude číšnice: Kariéry umělkyň v akademickém prostředí, feministická pedagogika a figura autority. - Zuzana Štefková (Gender a Výzkum, 2013)
The article tracks the journeys of selected American women artists of the second wave of feminist movement on their path through art institutions and their changing relation toward the figure of authority from the position of students to the one of art pedagogues. The text examines sexist conduct and language characteristic of and specific to the environment of art academies and the art world in general. Using the example of Feminist Art Program founded in 1970 by Judy Chicago at the Fresno University, it tries to assess power relations and teacher authority within the context of feminist art pedagogy. Furthermore, the text gives examples of problems encountered by Czech women artists regarding their access to authority. The article is based on a qualitative research and synthesis of interviews with American women artists who at some point of their careers taught studio art and tried to reconsider the authority they embodied.